2019
DOI: 10.1021/acsami.8b21214
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Shape Changing and Tristability of Bilayer Composite

Abstract: The programmable shape transition of a two-dimensional sheet to a three-dimensional (3D) structure in response to a variety of external stimuli has recently attracted increasing attention. Among the various shape changing materials, shape memory polymers (SMPs) can fix their temporary shape and/or their length and recover under proper thermal treatment. In this work, we create a bilayer composite by bonding one layer of elastomer with one layer of stretched SMPs, which can undergo a series of shape transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Our findings showed that PCHU displayed triple-shape-memory properties. Moreover, we further explored the shape-memory behaviors of the tensile strain of PCAU and orientation angle on its shape-changing procedure. The shape-memory behavior experiments were done at temperatures of 25, 45, 65, 45, and 25 °C with an external force. In addition, combining the experimental measurement with the theoretical prediction, shapes of the PCAU strips with different orientation angles θ = 0, 45°, 55°, 65°, and 90° are shown in Figure f.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed that PCHU displayed triple-shape-memory properties. Moreover, we further explored the shape-memory behaviors of the tensile strain of PCAU and orientation angle on its shape-changing procedure. The shape-memory behavior experiments were done at temperatures of 25, 45, 65, 45, and 25 °C with an external force. In addition, combining the experimental measurement with the theoretical prediction, shapes of the PCAU strips with different orientation angles θ = 0, 45°, 55°, 65°, and 90° are shown in Figure f.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, external stimuli, such as changes in light wavelength, [10,11] media pH, [12] environmental temperature, [13] exogenous chemicals, [14] applied electricity, [15] magnetic fields, [16] and specific biochemical signals, [17] modulate 4D hydrogel swelling and/or shrinking and produce macroscopic actuation. The integration of one or multiple stimuli into such responsive systems, such as gradient hydrogels, [18] single-component hydrogels (unimorph), [19] and bilayer [20] and trilayer [21] hydrogels, can impel the soft actuators to explicitly go through shape evolvement over time either in a preprogrammable fashion, referring to a defined shape morphing in the presence of predefined environmental conditions, or in an "on-demand" manner, referring to a regulated deformation under application of user-controlled external stimulation. Taking advantage of a stimuli responsive systems' programmability and controllability together with a specific geometrical design, hydrogel actuators are cast into 2D or 3D architectures [22] to carry out specific functions (e.g., transporting a cargo, [23] flow control, [24] and grasping [25] ) or locomotion (e.g., swimming [26] , walking [27] , and twisting [28] ).…”
Section: Introductionmentioning
confidence: 99%
“…Two classes of stimuli-responsive hydrogels are often used as active components for shape-morphing materials, i.e., the stimuli-induced swelling/deswelling hydrogels and shape memory hydrogels. For the first class, hydrogels are usually able to change their volume reversibly via expansion-shrinkage in response to different stimuli, such as pH, temperature, and solvent. For the second class, shape memory hydrogels (SMHs) are often able to fix temporary shapes and recover to their original shapes through formation–destruction reversible physical interactions or dynamic covalent bonds under external stimuli. Using the two classes of stimuli-responsive hydrogels as active components, various complex or 3D shapes can be achieved by the combination of active component and passive component via different deformation mechanisms (i.e., bending or buckling). …”
Section: Introductionmentioning
confidence: 99%